(منهج الشيخ حسنين مخلوف في تقرير صفات الله (دراسة تطبيقية من خلال تفسيره صفوة البيان لمعاني القرآن: The Methodology of Shaykh Ḥusaynīn Makhlūf in Affirming the Divine Attributes (An Applied Study through His Tafsīr Ṣafwat al-Bayān li-Maʿānī al-Qurʾān) - Ridwan Nur al-Salam (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study examines the methodology of Shaykh Ḥusayn Muḥammad Makhlūf in affirming the divine attributes of Allah through his exegesis Ṣafwat al-Bayān li-Maʿānī al-Qurʾān, a concise tafsīr that gained wide popularity among ordinary Muslims due to its clarity of expression and accessibility. The importance of this research lies in the potential risk of doctrinal deviations being transmitted through such concise works to the general readership, as well as the need to assess the extent to which this tafsīr adheres to the creed of the pious predecessors (al-salaf al-ṣāliḥ). The study employs a descriptive-analytical approach combined with a comparative method, by tracing the author’s interpretations concerning the divine attributes, weighing them against textual and rational evidences, and comparing them with the positions of the salaf and leading exegetes. The findings reveal that Makhlūf affirmed several major attributes—such as life, knowledge, power, speech, and transcendence (both in essence and in dominance)—in line with the methodology of the salaf. However, in other places, he adopted the path of tafwīḍ (consigning meanings) and taʾwīl (figurative interpretation), attributing tafwīḍ of meanings to the salaf, categorizing verses of transcendence and istiwāʾ as mutashābihāt (ambiguous), and interpreting certain attributes, such as seeing, hearing, face, and shin, away from their apparent meanings. This produced a methodological inconsistency between affirmation, tafwīḍ, and taʾwīl. The contribution of this study lies in highlighting the doctrinal dimensions of Ṣafwat al-Bayān, pointing out its methodological shortcomings, and guiding readers and scholars towards reliance on authoritative salafī exegeses, while offering a critical academic perspective that distinguishes between the genuine salaf methodology and its divergences.